Bavarian geographer’s Prissani and (Old) Prussians - Ardoino, Diego (Lietuvių kalba, 2017)
It is a widespread opinion in literature that the ethnonym Prussians is first encountered as the form Bruzi in a short Latin manuscript headed Descriptio civitatum et regionum ad septentrionalem plagam Danubii. Indeed among the 58 tribes listed in the Bavarian Geographer’s Descriptio there is another ethnonym, Prissani, which formally could be compared with the (Old) Prussians. On the base of the context in which the ethnonym is attested, of a thorough philological and linguistic examination of it and of onomastic data, the paper states that a) Prissani were probably settled in Moravia or not far from it, namely next to the region in which the Bavarian Geographer located the Bruzi; b) it is likely that Bruzi ir Prissani are corradicals and show different Latin ethnonym-forming suffixes; c) Bruzi and Prissani indicate the same tribe or two different groups of the same tribe; d) Bruzi and Prissani in the early Middle Ages have moved to the north, along the Vistula, from Moravia and the region located between the Rhine and the Enns rivers to the Prussia; e) we cannot say whether Bruzi and Prissani were really Balts or not.